The Representation of Racial Discrimination and Its Social Implications in Green Book (2018) - Febrian Agung Setia Budi; Titis Setyabudi (The Study Program of English Education of Palangka Raya University, 2026)
This study analyzes the representation of racial discrimination and its social implications in Green Book (2018). The film portrays the racial experiences of African Americans in the United States during the 1960s through the journey of Dr. Don Shirley, an African American pianist, and Tony Vallelonga, his driver. This research employs a qualitative descriptive method with a film analysis approach. The data consist of dialogues, scenes, character interactions, and narrative and cinematic elements depicting racial discrimination. The analysis integrates Feagin’s theory of racial discrimination, Hall’s theory of representation, Bordwell and Thompson’s film theory, Du Bois’s (1903) concept of double consciousness, and Bonilla-Silva’s theory of systemic racism to examine the forms, representation, and social implications of racial discrimination. The findings reveal four forms of racial discrimination represented in the film: individual discrimination, institutional discrimination, cultural racism, and spatial segregation, with institutional discrimination appearing most frequently. The study also finds several social implications, including identity struggle, power imbalance, social exclusion, and limited social mobility. These findings demonstrate that Green Book represents racism as a systemic social issue embedded in institutions, cultural values, and everyday interactions.